Preparation and evaluation of hand rub disinfectant - Padsalg, Amol; Jain, Devendra; Bidkar, Sanjay; Harinarayana, Dommati; Jadhav, Vijay (Asian Journal of Pharmaceutics (AJP), 2014)
The present work is to formulate effective hand rub disinfectant by selecting broad-spectrum antimicrobial and antifungal agents. Increased need of easy-to-use hand rub disinfectant in pharmaceutical, food processing industry, hospitals, and in clinical labs necessitated development of the best possible product. Formulations were prepared using Benzalkonium chloride, chlorhexidine gluconate as potent disinfectants along with alcohol 70%. In low concentration they were highly effective without leaving any toxic effect on the user’s skin. A synergistic effect was observed when ethyl alcohol 70% was used in combination. Suitable emollient and skin conditioning agents were used to avoid possible dehydrating effect on the user’s skin. Excellent volatility of the preparation was observed after use, leaving a thin antimicrobial film on the user’s hand. The use of suitable excipient brought effective removal of after the use leaving a soothening effect on the skin. The aim of present work is to develop hand rub formulation which evaporates quickly after applications leaving no trace on hands as in case of hand rub gels. The present formulation was found to be effective when compared with marketed liquid hand rub.